Parameters of treadmill exercise test and sympathetic activation are linked to the development of hypertension in subjects with high normal blood pressure. (14th October 2021) - Kalos, T; Dimitriadis, K; Konstantinidis, D; Tatakis, F; Drogkaris, S; Manta, E; Dri, E; Thomopoulos, C; Tousoulis, D; Tsioufis, K
Abstract: Background/Introduction: The clinical importance of a hypertensive response to exercise (HRE) in subjects with high normal blood pressure (BP) is not fully elucidated, while sympathetic overactivity followed by arterial stiffening are linked with development of hypertension. Purpose: The aim of this study was to assess parameters related to the development of hypertension in a 3 year follow in subjects with high normal BP. Methods: One hundred consecutive subjects with high normal office BP (54±8 years, 42 males, baseline office BP: 132/82 mmHg, 24-hour BP: 122/76 mmHg) at baseline underwent a negative for ischemia treadmill exercise test. Arterial stiffness was evaluated on the basis of carotid to femoral pulse wave velocity (PWV) values and sympathetic drive was assessed by muscle sympathetic nerve activity (MSNA) based on established methodology. SBP/MET-slope defined as: peak systolic BP–resting SBP)/(peak MET-1) was assessed. Follow up was scheduled every 6 months for 3 consecutive years, where BP was measured both in the office and with ambulatory blood pressure monitoring. End point was the development of hypertension diagnosed from office blood pressure measurements and confirmed from ambulatory blood pressure monitoring. Results: Patients who developed hypertension (n=35) compared to those who remained normotensives (n=65) had at baseline higher prevalence of HRE (75% vs. 13%, p=0.026), higher levels of carotid to femoral PWV (8.35 vs. 7.5 m/sec, p=0.043) and MSNA (37 vs. 31 bursts per minute, p=0.04), while their metabolic profile did not differ at the follow up (p=NS for all). In those who developed hypertension, SBP/MET-slope was higher in all Bruce protocol stages till peak exercise (stage 1: 6.25 vs. 4.25, stage 2: 7.6 vs. 5.3, peak exercise: 7.22 vs. 5.1; p<0.05 for all). Additionally, those who remained normotensives compared to those who developed hypertension exhibited a higher exercise capacity (10 vs. 11.5 METs, p<0.05) and maximal heart rate at peak exercise (154 vs. 164, p=0.001). Conclusion: In subjects with high normal BP, those who develop hypertension during follow-up are characterized by more frequent HRE accompanied with lower exercise capacity, arterial stiffening and sympathetic overactivation. These results suggest that exercise BP response, along with PWV and MSNA estimation could contribute to identify high normal BP subjects who are more prone to become hypertensives. Funding Acknowledgement: Type of funding sources: None.